2014
DOI: 10.1016/j.compositesa.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Aligned carbon nanotube reinforced high performance polymer composites with low erosive wear

Abstract: __________________________________________________________________________________________Please note that where the full text version provided on GALA is not the final published version, the version made available will be the most up-to-date full-text (post-print) version as provided by the author(s). Where possible, or if citing, it is recommended that the publisher's (definitive) version be consulted to ensure any subsequent changes to the text are noted. Citation for this version held on GALA:Chen, Jinhu, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Chen et al. 39 carried out experiments regarding erosion on unidirectional CF/EP composites as well as unidirectional and bidirectional CF/EP composites, filled with aligned carbon nanotubes (CNTs). The experiment data showed the maximum erosion wear rate at 30°–45° impingement angles for CNT film-reinforced epoxy composites, implying ductile erosion behaviour.…”
Section: Tribological Performance Of Carbon and Glass Fibre-reinforcementioning
confidence: 87%
“…Chen et al. 39 carried out experiments regarding erosion on unidirectional CF/EP composites as well as unidirectional and bidirectional CF/EP composites, filled with aligned carbon nanotubes (CNTs). The experiment data showed the maximum erosion wear rate at 30°–45° impingement angles for CNT film-reinforced epoxy composites, implying ductile erosion behaviour.…”
Section: Tribological Performance Of Carbon and Glass Fibre-reinforcementioning
confidence: 87%
“…Meanwhile, advanced scientific researches on these materials are progressively carried out. 16 Erosion wear is formed when solid particles moving at a certain velocity impact a surface and remove some materials off the top surface. Impingement angle (15°–90°), 7,8 velocity (≈16–88 m/s), 9 size (≈42–500 µm) and shape (spherical and angular) of the impacting particles (Garnet, SiC, Al 2 O 3 , and SiO 2 ), 10 as well as the properties of target material 1113 are important variables that affect the solid particle erosion behavior.…”
Section: Introductionmentioning
confidence: 99%
“…15 0 -30 0 ) then the erosion failure mode of a material is ductile in nature, On the contrary, if maximum rate of erosion occurs at higher impact angles (i.e. 70 0 -90 0 ) then the erosion failure mode of a material is brittle in nature (Arnold and Hutchings, 1992;Arnold and Hutchings, 1993;Zhou et al, 2013;Chen et al, 2014).…”
Section: Sand Erosion Wear Testmentioning
confidence: 99%
“…Based on the worn surface, they explained the failure phenomena. Chen et al (2014) observed erosion wear performance of carbon nanotube (CNT) film composites, which had two different orientations (uni-directional-0 0 , bi-directional-0 0 /90 0 ). Results show that unidirectional composite exhibits better erosion wear resistance than bi-directional composite.…”
Section: Introductionmentioning
confidence: 99%